2017
DOI: 10.1038/s41598-017-15827-2
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria as a simple predictor of incident diabetes over 8 years in the Korean Genome and Epidemiology Study (KoGES)

Abstract: Microalbuminuria (MAU) is a common subclinical disease and related with cardiovascular outcome both in diabetic and non-diabetic patients. However, there is rare data about the effect of MAU on the development of diabetes. Thus, we aimed to investigate whether MAU is associated with the development of incident diabetes. A total of 3385 subjects without diabetes (1503 men and 1882 women; mean age, 53 years) who participated in the Ansung–Ansan cohort study from 2001–2002 (baseline) to 2011–2012 (fifth follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Insulin stimulates store-operated Ca entry via Orai-1 channel in podocytes that makes actin remodeling and transepithelial albumin leakage resulting in microalbuminuria [ 35 ]. Recently over 8 years follow up study from Korean Genome and Epidemiology Study (KOGES) showed that microalbuminuria could be used as an early marker of progression to diabetes even in the non-prediabetic population [ 36 ]. Through microalbuminuria we could predict abnormal insulin resistance and diabetes, which were major risk factors for cardiovascular disease [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin stimulates store-operated Ca entry via Orai-1 channel in podocytes that makes actin remodeling and transepithelial albumin leakage resulting in microalbuminuria [ 35 ]. Recently over 8 years follow up study from Korean Genome and Epidemiology Study (KOGES) showed that microalbuminuria could be used as an early marker of progression to diabetes even in the non-prediabetic population [ 36 ]. Through microalbuminuria we could predict abnormal insulin resistance and diabetes, which were major risk factors for cardiovascular disease [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential limitations, our results provide valuable insights into the impact of MHO on diabetes development through a causal inference method based on time‐varying exposure. We considered physician diagnosis and medication use to identify as many patients with diabetes as possible, similarly to previous studies 45,46 . Also, results derived from long‐term follow‐up preclude the possibility of early follow‐up bias 11 .…”
Section: Discussionmentioning
confidence: 99%
“…There is further evidence that the presence of MAU in prediabetes could be an early indicator for the development of DM. A 10-year cohort study conducted in participants with MAU without DM showed that people with MAU were more likely to develop DM, even after adjustment for the presence of prediabetes [ 75 ]. Similarly, a Chinese cohort study showed that MAU was associated with increased risk of diabetes after a three-year follow-up in populations with normal glucose tolerance and impaired glucose regulation.…”
Section: Prediabetes and Microcirculationmentioning
confidence: 99%